Emotional intelligence in schools : a comprehensive approach to developing emotional literacy - Krefft, Katherine (New York : Routledge, 2019)
"This text presents a methodical, organized approach to counseling students in emotional intelligence (EI) by detailing how to understand and direct emotions, while also keying counselors directly to the underlying emotional motivations behind the behaviors. Divided into four units, the book starts with an overview of emotions and continue to explore the nature of anger, fear, grief, and guilt. Chapters present both explanatory narratives and teen-centered activities to show how these challenging, uncomfortable feelings when unregulated may negate resiliency and lead to anxiety, bullying, depression, and teen suicide. Counselors and educators alike will benefit from the light, unexacting tone that encourages humor and levity and discusses how to handle difficult emotions without harsh and heavy overtones"--
Includes index.
Keywords: Educational counseling; Emotions in adolescence; Emotions in children; Emotional intelligence